Analisis Penerimaan Pengguna Aplikasi Green SM Menggunakan Kerangka Pengembangan Technology Acceptance Model (TAM) Dengan Variabel Social Influence Di Kota Surabaya - Reisya Nasywa Rahmadina; Ghea Sekar Palupi (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The development of application-based transportation, particularly Green SM, encourages the use of environmentally friendly technology. Although it offers convenience for users and has a high number of downloads and ratings, this does not necessarily reflect sustainable use. Therefore, this study aims to analyze the factors that influence the acceptance and use of the Green SM application using the development of the Technology Acceptance Model (TAM) with the addition of the Social Influence variable. This study uses a quantitative approach with the Partial Least Squares-based Structural Equation Modeling (PLS-SEM) method processed using SmartPLS 4 software involving 191 respondents who use the Green SM application in Surabaya City. The results show that the Perceived Ease of Use variable has a significant effect on Perceived Usefulness, but does not have a significant effect on Behavioral Intention. Meanwhile, the Perceived Usefulness variable has a significant effect on Behavioral Intention. The Social Influence variable has a significant effect on Behavioral Intention. Furthermore, the Behavioral Intention variable has a significant effect on Actual System Use. The results of this study indicate that the main factors influencing the use of the Green SM application are perceived benefits and social influence, while ease of use does not directly affect the intention.